Physical modulation and peripheral nerve regeneration: a literature review - Xiangwen Zhai; Yuzhong Wang (Cell Regeneration)
Abstract Peripheral nerve injury (PNI) usually causes severe motor, sensory and autonomic dysfunction. In addition to direct surgical repair, rehabilitation exercises, and traditional physical stimuli, for example, electrical stimulation, have been applied in promoting the clinical recovery of PNI for a long time but showed low efficiency. Recently, significant progress has been made in new physical modulation to promote peripheral nerve regeneration. We hereby review current progress on the mechanism of peripheral nerve regeneration after injury and summarize the new findings and evidence for the application of physical modulation, including electrical stimulation, light, ultrasound, magnetic stimulation, and mechanical stretching in experimental studies and the clinical treatment of patients with PNI.